Endovascular treatment of May-Thurner syndrome-associated iliofemoral deep vein thrombosis in a 76-year-old woman. - Chang Hoon Oh (16786347) (2025)
A. Contrast-enhanced computed tomography venography showing compression of the left common iliac vein (LCIV) by the overlying right common iliac artery and L4 vertebral body (arrow), consistent with May-Thurner syndrome. B. Conventional venography reveals a prominent venous spur and > 50% luminal narrowing at the LCIV (arrowhead), along with collateral venous flow (asterisk). C. Post-stenting venogram after the deployment of a 14-mm self-expandable stent demonstrating complete resolution of venous stenosis, spur formation, and collateral flow.